Author Correction: Drug-mediated metabolic tipping between antibiotic resistant states in a mixed-species community. Issue 11 (November 2018) - Beardmore, Robert; Cook, Emily; Nilsson, Susanna; Smith, Adam; Tillmann, Anna; Esquivel, Brooke; Haynes, Ken; Gow, Neil; Brown, Alistair; White, Theodore; Gudelj, Ivana
In the version of this Article originally published, the following sentence was missing from the Acknowledgements: "R.E.B. is an EPSRC Healthcare Technologies Impact Fellow EP/N033671/1; I.G. is funded by ERC Consolidator grant 647292 MathModExp; A.J.P.B., N.A.R.G. and A.T. were funded by BBSRC grant BB/F00513X/1; K.H., I.G., S.N. and E.C. were funded by BBSRC grant BB/F005210/2." This text has now been added.